A non-binary biopharmaceutical classification of drugs: The AB Gamma system - Macheras, Panos; Karalis, Vangelis (INTERNATIONAL JOURNAL OF PHARMACEUTICS, 2014)
The purpose of the present work is to develop a non-binary biopharmaceutical classification system the so called AB Gamma system. The original mathematical model used for the development of BCS, appropriately modified, was applied to estimate the limiting values of drug solubility and permeability when the fraction of dose absorbed, Fa, was 0.90 or 0.20. The AB Gamma system is based on the fraction of dose absorbed and relies on permeability, solubility plane. The first category (A, alpha) includes drugs with Fa = 0.90, whereas the B (beta) category consists of drugs with Fa = 0.20. The area lying between the two boundaries of A and B defines the third category (gamma), Gamma, (0.20 < Fa < 0.90). For comparative purposes, the BCS classes I-IV were co-plotted together with the AB Gamma system. Most of the BCS classes II and III are included in category Gamma which mainly consists of drugs with properties like moderate or low solubility and permeability. Due to the dynamic character of dissolution and uptake processes, category A is expanded toward BCS Class II. The AB Gamma system allows the classification of all compounds into three categories (A, B, Gamma) in terms of the fraction of dose absorbed. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: Dose; Fraction of dose absorbed; Non-binary BCS; Permeability; Simulations; Solubility